(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The experiment was carried out at FSRD site, Kadamshahar, Godagari, Rajshahi during 2009-10 and 2010-11 to find out the number of seed stalk and optimum boron dose for seed production of summer onion in High Barind Tract (AEZ 26). The treatments comprised three levels of seed stalk (0, 4, and 6) and three rates of boron application (0, 1, and 2 kg/ha). It revealed that the seed stalks and boron either in single or combination had significant effect on the yield and yield contributing characters of onion seed. The combination comprising 4 stalks with 2 kg B/ha and 6 stalks with 1 kg B/ha were found to be the best choice for achieving higher seed yield of onion. The highest seeded fruit/umbel (4.06 and 4.55) and seed yield (669 and 713 kg/ha) were recorded from 6 stalks/plant fertilized with 1 kg boron/ha which was statistically identical to 6 stalks/plant fertilized with 2 kg boron/ha and 4 stalks/plant with 2 kg/ha boron in the High Barind Tract. DOI: http://dx.doi.org/10.3329/bjar.v38i4.18870 Bangladesh J. Agril. Res. 38(4): 573-578, December 2013